Faktor - Faktor Yang Berhubungan Dengan Kejadian Tinea Pedis Pada Pemulung Di TPA Jatibarang Semarang - Kurniawati, Ratna Dian; Suhartono, Suhartono; Hanani D., Yusniar (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2006)
ABSTRACT Background : Tinea pedis is a parasit disease caused by the dermatopoyd fungi and found on skin around sole of foot and toe. Several risk factors of Tinea pedis are as follow: wearing the shoes for whole day, wearing the sock while working, and hight exposure of fungi. The aim of this research was to determine relationship between the living environment and the incidence of Tinea pedis on